Industrial relations and labor movement in Bangladesh - Ahmad, Iqbal (Professor of human resource management and marketing management) (Dhaka : Ferdous Iqbal, 2014)
A comprehensive collection of various aspects of industrial relation and labour movement in Bangladesh.
Includes bibliographical references
In English.
Keywords: Industrial relations -- Bangladesh; Labor movement -- Bangladesh